Application of semi-active tuned mass dampers to base excited systems. - Setareh, Mehdi (Earthquake engineering & structural dynamics.)
A continously variable semi-active damper is used in a tuned mass damper (TMD) to reduce the level of vibration of a single degree of freedom system subjected to harmonic base excitations. The ground hook dampers as have been used in the auto industry are being studied here. Using these dampers a new class of tuned mass dampers, named as ground hook tuned mass dampers (GHTMD) is being introduced. In order to generalize the design properties of the GHTMDs, they are defined in terms of non-dimensional parameters. The optimum design parameters of GHTMDs for lightly damped systems are obtained based on the minimization of the steady state displacement response of the main mass. These parameters are computed for different mass ratios and main system damping ratios. Frequency responses of the resulting systems are compared to that of equivalent TMDs using passive dampers. In addition, other characteristics of this system as compared to the passive TMDs are discussed. A design guide to obtain the optimum parameters of GHTMD using the developed diagrams in this paper based on non-dimensional values is presented.